Innovative Leadership as a Catalyst in the Change of Idiot Village into Creative Village Stigma - Pramono, Joko; Suwardi; Khan , Zubair Ahmed (Journal of Local Government Issues, 2025)
Karangpatihan village in Balong Sub District, Ponorogo Regency, East Java is an example of competent village with rapid development trend. Viewed from evolution, empowerment, and development aspects, this village is inseparable from innovative leadership implemented by a Village Head named Eko Mulyadi. Eko Mulyadi has received many awards for successfully reducing the stigma of idiot village for Karangpatihan village by means of training the people belonging to idiot category. This research aims to analyze and describe innovative leadership implemented to change the stigma of an idiot village into a creative village. Innovation made by Eko Mulyadi has been embodied in social and creative economic empowerment, such as catfish breeding and training for producing batik ciprat (splash batik) as a basic icon. The research method used is an empirical model that is descriptive in nature with a qualitative approach. The research focuses on individuals and the ability to influence groups or organizations in Karangpatihan Village. The research results show that Eko Mulyadi's leadership has catalyzed the big change, as it is equipped with a unique strategy, idea, and method that can change the physical shortcomings of idiot people into their strengths. In conclusion, Eko Mulyadi's leadership belongs to innovative leadership as it indicates the result.